Childism and the Politics of Social Empowerment - John Wall Wall (Sociedad e Infancias)
The argument made here is that childism advances a new critical theory for understanding what is involved in social empowerment. Like feminism, decolonialism, and other critical perspectives, its aim is to reimagine human relations not just for one particular group but for all as members of shared social systems. Childism is first examined as a response to the normative problem of historical adultism or patriarchy, the empowerment of adulthood by disempowering childhood. Then it is formulated as a critical theory of its own based on new conceptions of the political subject, public expression, and political empowerment (or, respectively, the ontological, epistemological, and political dimensions of social life). These are illustrated in relation to questions of voting rights, climate activism, free speech, and work. The result is a theory of social empowerment that calls for the active inclusion of all persons in systems of power specifically in their deeply interdependent lived experiences of difference.